Public Electricity Provision and Performance of Manufacturing Firms in Nigeria - Tata, Ibrahim Abba (2012)
This study examined how public electricity power provision affects the performance of manufacturing firms in Nigeria. The study applied regression analysis using ordinary least square (OLS) techniques; the features of the electricity market in Nigeria were also analyzed. One strong outcome of the study is that the growth of manufacturing firms in Nigeria is positively and significantly influenced by electricity power supply. We showed that when public power sector in Nigeria is privatized, as a strategy for restructuring electricity market, competition in the sector will tend to prevail coupled with efficiently supply of power, leading to manufacturing firms reaching their required demand for electricity in the production process and hence promote their level of output.